AN AUDIT OF THE PAEDIATRIC EMPIRIC ANTI-INFECTIVE GUIDELINES AND ANTI-INFECTIVE DRUG DOSE TABLE FOR CHILDREN. Issue 9 (17th August 2016) - Zaffar, Sanna; Fletcher, Penny
Abstract : Aim: To assess compliance with paediatric empiric anti-infective guidelines and anti-infective drug dose table for children. Method: Data collection was carried out on the paediatric wards. Exclusions: ▸ Bone marrow transplant patients (BMT). ▸ Patients not on empirical anti-infective treatment Data were collected prospectively between January and 30 February 2015. A data collection form was completed and data analysed using Excel. Standards: (1) 90% adherence to the paediatric guidelines for empirical anti-infectives treatment (2) 90% prescriptions have the indication recorded in either the drug charts or notes (3) 90% prescriptions have duration recorded of treatment/review date on drug chart or medical notes (4) 95% initial doses should adhere to the anti-infective drug dose table for children Results: Data were collected from 50 patients; eight were subsequently excluded as they were not on empirical treatment or were prescribed antibiotics started prior to admission giving a final sample for analysis of 42. 40/41 prescriptions (98%) adhered to the paediatric guidelines for the empirical treatment prescribed. 1 of 41 prescriptions (2.4%) did not. Exclusion criteria: One indication was not within guidelines ('abscess'). 40/42 prescriptions (95%) stated the indication for the anti-infective. 2 (5%) required prompting from the pharmacist. 14 out of 42 (33%) had the indication documented in the notes and 28 (67%) on the drug chart. 26/42 prescriptions (62%) had a record of the duration of treatment/review date on the drug chart/notes. Of the 26 prescriptions with a recorded duration of treatment, 2 (8%) were found in the notes and 24 (92%) were found in the drug chart. 67/69 (97%) of the initial doses adhered to the anti-infective drug dose table for children. 2 out of 69 (3%) did not. Conclusions: Standard 1 passed, this shows an improvement from the last audit of the guidelines in 2013 (of 72% adherence). In one case the indication of the antibiotic was not within the guidelines, which should be amended. Standard 2 passed—However, most of the indications were found in the notes, with clear documentation space on the drug chart it would be useful to have the indication in the drug chart. There has been a significant improvement from the previous audit carried out (from 16%). Standard 3 did not meet the adherence requirement expected. However, there has been an improvement from 14% from last year. Standard 4 (not been previously audited) suggests that the drug dosing table is also clear in providing guidance. Two data were excluded from the overall data as cefuroxime and rifampicin are not in the guidelines. Overall, the main need for improvement is having the duration of treatment documented. To achieve improvement in all standards would require: ▸ Presenting the results to the antibiotic stewardship and pharmacy team. ▸ Implementing an electronic prescribing system which prompts for completion of essential fields. ▸ Updating and renewing the antibiotic Smart-phone App. ▸ Compulsory education sessions for the junior doctors by the antibiotic stewardship team.